Dysregulation of Galectin-3. Implications for Hermansky-Pudlak Syndrome Pulmonary Fibrosis - Cullinane, Andrew R. (American Thoracic Society, 2014)
The etiology of Hermansky-Pudlak syndrome (HPS) pulmonary fibrosis (HPSPF), a progressive interstitial lung disease with high mortality, is unknown. Galectin-3 is a β-galactoside–binding lectin with profibrotic effects. The objective of this study was to investigate the involvement of galectin-3 in HPSPF. Galectin-3 was measured by ELISA, immunohistochemistry, and immunoblotting in human specimens from subjects with HPS and control subjects. Mechanisms of galectin-3 accumulation were studied by quantitative RT-PCR, Northern blot analysis, membrane biotinylation assays, and rescue of HPS1-deficient cells by transfection. Bronchoalveolar lavage galectin-3 concentrations were significantly higher in HPSPF compared with idiopathic pulmonary fibrosis or that from normal volunteers, and correlated with disease severity. Galectin-3 immunostaining was increased in HPSPF compared with idiopathic pulmonary fibrosis or normal lung tissue. Fibroblasts from subjects with HPS subtypes associated with pulmonary fibrosis had increased galectin-3 protein expression compared with cells from nonfibrotic HPS subtypes. Galectin-3 protein accumulation was associated with reduced Galectin-3 mRNA, normal Mucin 1 levels, and up-regulated microRNA-322 in HPSPF cells. Membrane biotinylation assays showed reduced galectin-3 and normal Mucin 1 expression at the plasma membrane in HPSPF cells compared with control cells, which suggests that galectin-3 is mistrafficked in these cells. Reconstitution of HPS1 cDNA into HPS1-deficient cells normalized galectin-3 protein and mRNA levels, as well as corrected galectin-3 trafficking to the membrane. Intracellular galectin-3 levels are regulated by HPS1 protein. Abnormal accumulation of galectin-3 may contribute to the pathogenesis of HPSPF.